THE EFFECT OF ICT-BASED INTERACTIVE GAME ON ENGLISH ACHIEVEMENT IN THE PRIMARY SCHOOL IN BULELENG - ., Pt. Febry Budi Hendrawan; ., Dra.Ni Made Ratminingsih, MA; ., Made Hery Santosa, S.Pd, M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
The aim of this study is to find out the effect of ICT-based interactive game towards the English achievement of sixth grade students in primary school cluster IV in Sukasada district, in academic year 2016/2017. This study was a quasi-experimental research which used post-test only control group design. The population of this study was 174 students from eight elementary schools in cluster IV in Sukasada district. The samples of this study were 22 students of sixth graders in SD Negeri 3 Sukasada and 22 students of sixth graders in SD Negeri 4 Sukasada selected by administering cluster random sampling technique. The data were analyzed quantitatively by using descriptive and inferential statistics analysis. It was found that the result of hypothesis testing (independent t-test) showed that the tobs = 3.256>tcv= 2.018 and the significance value of the data was 0.002 lower than α = 0.05. It can be inferred that there is a significant effect of ICT-based interactive towards students’ English achievement. In conclusion, ICT-based interactive game is an effective teaching media and it is suggested to be applied by teachers to improve students’ English achievement in primary schools. keyword : English achievement, ICT-based interactive game, young learners